Personal Demobilization of the Polish Army in 1945–1947 - Jarno, Witold (Social consequences of war, 2024)
The article discusses the process of personal demobilization carried out in the Polish Army in 1945–1947. It consisted in the gradual dismissal from the army of soldiers serving in it during World War II and reducing the size of the army, adapting it to the assumptions of its peaceful organization. The final result of this process was the transition in October 1947 to a system of military service covering two age groups at a time. The process of personal demobilization of the Polish Army was not easy and quick, but despite many problems, it was managed to be carried out efficiently and on time. The aim of the article is to discuss the assumptions of this process and the course of its individual phases, which are based essentially on archival documents. The literature on the subject was also used to the extent necessary, as it often contains divergent data on the process of demobilization, which required confronting it with the information contained in the archives.